INTEGRATING ECONOMIC SELF-RELIANCE INTO ISLAMIC BOARDING SCHOOL EDUCATIONAL MANAGEMENT - Sarah Kustini; Subaidi Subaidi; Muhammad Khoiruddin (PROCEEDING OF INTERNATIONAL CONFERENCE ON EDUCATION, SOCIETY AND HUMANITY, 2026)
This research was conducted to analyze the influence of integrating economic independence into education management within the pesantren (Islamic boarding school) environment as an effort to strengthen its functions as an institution for education, da'wah, and community empowerment. Amidst the challenges of globalization, pesantrens are required not only to serve as centers for religious knowledge transmission (tafakkuh fiddin) but also to be adaptive to contemporary developments by transforming into social entities that drive a self-reliant Sharia economic movement. This study employs a descriptive qualitative approach with library research method to examine the positive impacts and dissect the strategies for merging entrepreneurship curricula with productive business units. The results indicate that the integration of economic independence is implemented through three main pillars: the optimization of pesantren assets via business units (such as Kopontren/cooperatives, agriculture, livestock, services, and MSMEs), the development of an entrepreneurial spirit (santripreneur), and the utilization of digital technology within the pesantren financial ecosystem. The conclusion asserts that economic independence, when effectively integrated with pesantren education management, can reduce institutional reliance on external aid, enhance the quality of core educational facilities, and produce graduates who are economically independent without abandoning spiritual values.